Perbandingan Biaya dan Waktu Metode Permen PU No. 28 Tahun 2016 Dengan Metode Kontraktor (Studi Kasus: Proyek Student Apartement Building Block 1 (Female) UIII Depok) - Abimanyu, Muhammad Aqila; Pramono, Didiek (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The Ministry of PUPR makes a standard unit price of work by issuing the Minister of Public Works Regulation No. 28 of 2016. However, the total cost to be incurred is greater than the method used by the contractor. So the analysis of construction costs is needed as a means to improve the efficiency and effectiveness of development activities in the construction sector. Planning a project cost budget is one of the absolute activities before carrying out a development. The purpose of this final project is to calculate the Budget Plan (RAB) for the Student Apartment Building Block 1 (Female) UIII Depok project by using the Minister of Public Works Regulation No. 28 of 2016 and using the journal unit prices for construction materials and buildings in the Jakarta area. After being analyzed, the total costs that must be incurred for construction using the Minister of Public Works Regulation No.28 of 2016 on the Student Apartment Building Block 1 (Female) UIII Depok project are Rp. 63,180,745,237. As for the construction with the contractor method, it only costs Rp.44,211,810,456. When compared, the difference between the two methods is around Rp. 18,968,934,781 or 30.02%.